2013
DOI: 10.5830/cvja-2013-002
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and associated factors in older adults in South Africa : cardiovascular topics

Abstract: BackgroundOlder adults are disproportionately affected by hypertension, which is an established risk factor for cardiovascular disease. Little attention has been focused on hypertension and associated factors among older adults in Africa. Therefore, this study aimed to investigate the prevalence and associated factors of hypertension in a national sample of older South Africans who participated in the Study of Global Ageing and Adults’ Health (SAGE) in 2008.MethodsIn 2008 we conducted a national, population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
101
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 32 publications
19
101
5
1
Order By: Relevance
“…A little attention had been focused on hypertension and associated factors among older adults in Africa [8]. In one study of hypertension and associated factors in older adults in South Africa, it was found that hypertension was more prevalent (77.3%) among older adults aged 50 years and more in South Africa and it is prevalent in Rwanda at a rate of 41% and 36.6% for men and women respectively [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A little attention had been focused on hypertension and associated factors among older adults in Africa [8]. In one study of hypertension and associated factors in older adults in South Africa, it was found that hypertension was more prevalent (77.3%) among older adults aged 50 years and more in South Africa and it is prevalent in Rwanda at a rate of 41% and 36.6% for men and women respectively [8].…”
Section: Introductionmentioning
confidence: 99%
“…In one study of hypertension and associated factors in older adults in South Africa, it was found that hypertension was more prevalent (77.3%) among older adults aged 50 years and more in South Africa and it is prevalent in Rwanda at a rate of 41% and 36.6% for men and women respectively [8]. Since the blood pressure tends to rise as individual becomes older, high blood pressure is frequently found in old people compared to other age group [7] [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…[1] The same report also indicates that hypertension is most prevalent in the African region, where about 46% of adults above the age of 25 years are affected. In South Africa, not only is hypertension the commonest diagnosis and reason for clinic attendance among adults attending primary care, [2] it is also the 2 nd leading cause of death 2 [3]. About 25% of the general adult population are reported to be affected by hypertension [4,5] but prevalence of up to 77.3% have been reported among people older than 50 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…About 25% of the general adult population are reported to be affected by hypertension [4,5] but prevalence of up to 77.3% have been reported among people older than 50 years of age. [2] Hypertension is a major risk factor for cardiovascular disease (CVD) and increases the risk of morbidity and mortality from stroke, coronary heart disease, heart failure and renal failure. [6] It accounts for at least 45% to 51% of the global deaths from ischemic heart diseases and strokes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation